2022
DOI: 10.1097/prs.0000000000010073
|View full text |Cite
|
Sign up to set email alerts
|

Oral antibiotics do not prevent infection or implant loss after immediate prosthetic breast reconstruction: Evidence from 683 consecutive reconstructions without prophylaxis.

Abstract: Background: Infectious complications following implant-based postmastectomy breast reconstruction (PMBR) are a significant cause of morbidity. Nationwide, antimicrobial stewardship efforts have sought to reduce the use of prophylactic antibiotics postoperatively. However, there are conflicting data regarding the utility of extended antibiotic prophylaxis (EAP) after PMBR, and many surgeons continue to prescribe them. Methods: The authors conducted a retrospective study of 1077 women who underwent immediate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Following an assessment of 675 relevant papers, 18 papers that were released between 2009 and 2023 were included in the meta‐analysis since they matched the inclusion criteria 11,12,24–39 . Table 2 summarises the findings of these investigations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following an assessment of 675 relevant papers, 18 papers that were released between 2009 and 2023 were included in the meta‐analysis since they matched the inclusion criteria 11,12,24–39 . Table 2 summarises the findings of these investigations.…”
Section: Resultsmentioning
confidence: 99%
“…The sample size was 37-7398 people. 11,12,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] The examined data revealed that systemic antibiotic prophylaxis had a T A B L E 1 Database search strategy for inclusion of examinations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…86 Antibiotics and drain placement are routinely used to reduce postoperative infection and seromas, but effectiveness depends on timing, duration, procedure, and patient risk factors. 87,88 While literature suggests postoperative approaches such as NPWT, antibiotics, and…”
Section: Postoperative Preventionmentioning
confidence: 99%
“…[5][6][7][8][9] A prolonged course of systemic, oral antibiotics has not shown evidence-based benefit. 10,11 Selective, prophylactic, local delivery of antibiotics may provide the therapeutic effect of antibiotics while avoiding systemic side effects and other issues of antibiotic overuse. 12,13 Absorbable antibiotic beads have been well described for orthopedic procedures for osteomyelitis, as well as pressure sore reconstruction for ulcer recurrence, and vascular graft infection.…”
mentioning
confidence: 99%